In a text that I am reading, they state that the following partial fraction ($r$ fixed) expansion is "readily computed":

$$f(z) = \frac{z^r}{(1-z)(1-2z)(1-3z)\cdots (1-rz)} = \frac{1}{r!} \sum_{j=0}^r \binom rj \frac{(-1)^{r-j}}{1-jz}$$

I know how to do partial fractions, or at least I thought I did. I tried to set it up with something like $$\frac{A_1}{1-z} + \frac{A_2}{1-2z} + \cdots + \frac{A_r}{1-rz}$$ but it got messy. Also, the answer given above has a constant term $\frac{(-1)^{r}}{r!}$ when $j=0$, which shouldn't show up when doing this method normally.

Could someone point me in the right direction? Thanks!

I now see why the constant term is necessary; doing a "long division" would result in the $\frac{(-1)^r}{r!}$ term. The remainder would be something like $$\frac{z^r - \frac{1}{r!}(1-z)(1-2z)\cdots(1-rz)}{(1-z)(1-2z)\cdots(1-rz)}$$ which technically could be solved by partial fractions...

Induction also looks promising, as suggested by Maesumi.

  • $\begingroup$ The first thing to do is to convince ourselves that this equation produces correct results. When $r = 1$, we have $z/(1-z) = -1/(z-1)-1$. When $r = 2$, we have $z^2/((1-2 z) (1-z)) = -1/(2 (2 z-1))+1/(z-1)+1/2$ $\ldots$. Notice that in both cases we have a constant. Use the Summation and make sure you get the same thing as I used another approach. Next, are you trying to derive or prove the result? $\endgroup$
    – Amzoti
    May 26 '13 at 21:43
  • 1
    $\begingroup$ The constant term is necessary because power of numerator and denominator are equal to $r$. Saying it is "readily computed" could be author's humor! So don't feel bad if it is not obvious. Have you tried induction? $\endgroup$
    – Maesumi
    May 26 '13 at 21:53
  • $\begingroup$ Try to use the formula I introduced in this problem. $\endgroup$ Jun 17 '13 at 20:58

The coefficient of $\frac{1}{1-kz}$ is $$\left[\frac{z^r}{(1-z)(1-2z)(1-3z)\cdots\widetilde{(1-kz)}\cdots (1-rz)}\right]_{r=\frac{1}{z}}=\frac{\left(\frac{1}{k}\right)^r}{(1-\frac{1}{k})(1-2\frac{1}{k})(1-3\frac{1}{k})\cdots\widetilde{(1-k\frac{1}{k})}\cdots (1-r\frac{1}{k})}=\frac{1}{k(k-1)(k-2)\cdots\widetilde{0}(-1)(-2)\cdots(k-r)}=\frac{1}{r!} \binom rj (-1)^{r-j}$$


Multiply by $\frac{1}{1-jz}$ and plug in $\frac{1}{j}$ to get \begin{align*} A_j&=\frac{1/j^r}{\left( 1-\frac{1}{j} \right)\left( 1-\frac{2}{j} \right)\cdots \left( 1-\frac{j-1}{j} \right)\left( 1-\frac{j+1}{j} \right)\cdots \left( 1-\frac{r}{j} \right)} = \\ &= \frac{1}{j\left( j-1 \right)\left( j-2 \right)\cdots \left( j-j+1 \right)\left( j-j-1 \right)\cdots \left( j-r \right)}= \\ &= \frac{1}{\underbrace{j\left( j-1 \right)\left( j-2 \right)\cdots 1}_{j!} \cdot \underbrace{(-1)(-2) \cdots (-(r-j))}_{(-1)^{r-j}(r-j)!}}= \\ &= \Big\{\binom{r}{j} = \frac{r!}{j!(r-j)!}\Big\}= \frac{1}{r!}\binom{r}{j}\left( -1 \right)^{r-j} \end{align*}

By polynomial division, we can write \begin{equation} \frac{z^r}{(1-z)(1-2z)\cdots (1-rz)}=q+\frac{c}{(1-z)(1-2z)\cdots (1-rz)}\tag{1} \end{equation} where $q, c\in \mathbb{R}$. By theory of partial fractions, we can have at most $r$ fractions, so by the above, we get \begin{equation*} \frac{c}{(1-z)(1-2z)\cdots (1-rz)}=\sum_{j=1}^{r}\frac{A_j}{1-jz} \end{equation*} Plugging in $0$ in (1), we thus obtain \begin{align*} q=A_0&=-\frac{1}{r!}\sum_{j=1}^{r}\binom{r}{j} \frac{(-1)^{r-j}}{1-0}= \\ &=-\frac{1}{r!}\Big[\underbrace{\sum_{j=0}^{r}\binom{r}{j}(-1)^{r-j}}_{(1-1)^r=0}-\binom{r}{0}(-1)^r \Big]=\frac{(-1)^r}{r!} \end{align*}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.